A comparative analysis of ultrasound and serology for the diagnosis and post-treatment monitoring of cystic echinococcosis in experimentally infected sheep - Celik, Figen; Simsek, Sami; Ceribasi, Songul; Uslug, Muhammet; Han, Mehmet Cengiz (Elsevier, 2025)
Cystic echinococcosis (CE) is one of the most significant zoonotic diseases globally, affecting both humans and livestocks. The aim of this study was to compare the efficacy of ultrasound (US) and serological methods as early diagnostic markers for both post-infection and post-treatment follow-up of CE in experimentally infected sheep. An hydatid cyst fluid was aspirated and 20,000 viable protoscoleces were administered orally to a dog. After 50 days, all adult parasites were collected. The eggs were extracted and used for the experimental infection of 14 lambs (11 experimental and 3 control). Blood samples were collected and US imaging were performed weekly. Partially purified hydatid cyst fluid (PPHCF) and recombinant paramyosin (EgPmy5) antigens were prepared. The sensitivity of PPHCFA (95 %) was observed to be higher than that of rEgPmy5 (70 %), yet the cross-reaction rates with other helminth infections were 95 % and 20 %, respectively. The cysts first time were imaged at the 8 month after infection by US. Albendazole (7.5 mg/kg) treatment was initiated in the eighth month of the experimental infection. Six sheep were treated with albendazole every 30 days for a period of three months. In two sheep which died on the 8th and 10th day of the treatment, it was observed that the tension in the cyst membrane had disappeared due to a reduction in fluid and fibrosis in the cysts in the liver. Following a threemonth treatment, the majority of cysts in the liver had reduced in size to approximately that of a pinhead, and the overall number of cysts had decreased in comparison with the control sheep. After a six-month treatment the presence of fibrotic, pinhead-sized cysts devoid of fluid was observed in the liver. Seropositivity was detected in a sheep with PPHCFA and another sheep with rEgPmy5 from the seventh day of experimental infection and remained detectable till death. In conclusion, albendazole can induce deformation in hydatid cysts as early as the first week of treatment and PPHCF antigen can be used for serological monitoring of the sheep population.
Keywords: Echinococcus granulosus; Sheep; Ultrasound; Western blot; Antigen